2022
DOI: 10.3390/ijms232012447
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-19b Plays a Key Role in 5-Fluorouracil Resistance and Predicts Tumor Progression in Locally Advanced Rectal Cancer Patients

Abstract: The standard clinical management of locally advanced rectal cancer (LARC) patients includes neoadjuvant 5-fluorouracil (5-FU)-based chemoradiotherapy (CRT) followed by mesorectal excision. MicroRNA (miR)-19b expression levels in LARC biopsies obtained from initial colonoscopy have recently been identified as independent predictors of both patient outcome and pathological response to preoperative CRT in this disease. Moreover, it has been discovered that this miR increases its expression in 5-FU resistant colon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 51 publications
3
4
0
Order By: Relevance
“…We first explored how miR-19b modulates cell viability, which was significantly enhanced after miR-19b overexpression, and reduced when this miR was silenced (Figure 1). These findings were concordant with the observed results in our previous work when we analyzed the effect of miR-19b in determining 5-FU sensitivity [30]. As expected, PPP2R5E overexpression significantly impaired cell viability whereas its silencing led to increased cell viability (Figures S1 and S2), suggesting that miR-19b-induced effects are at least partially mediated by its role as negative PPP2R5E regulator.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…We first explored how miR-19b modulates cell viability, which was significantly enhanced after miR-19b overexpression, and reduced when this miR was silenced (Figure 1). These findings were concordant with the observed results in our previous work when we analyzed the effect of miR-19b in determining 5-FU sensitivity [30]. As expected, PPP2R5E overexpression significantly impaired cell viability whereas its silencing led to increased cell viability (Figures S1 and S2), suggesting that miR-19b-induced effects are at least partially mediated by its role as negative PPP2R5E regulator.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, miR-19b predicts shorter overall survival and metastatic progression in CRC patients [28]. In concordance, previous studies from our group showed that miR-19b is highly deregulated in LARC, and predicts both patient outcome and pathological response to neoadjuvant chemoradiotherapy (nCRT), and cancer progression in this disease, observing higher recurrence rates in patients with high miR-19b levels [29,30]. Moreover, PP2A regulatory subunit PPP2R5E was able to predict the response to nCRT in our LARC patient cohort, confirming the inverse correlation that exists between miR-19b and PPP2R5E expression in this disease [29].…”
Section: Introductionsupporting
confidence: 78%
See 1 more Smart Citation
“…This finding of miR-19b and correlation with tumour response is supported by other studies in the literature, mainly in solid tissue [ 31 , 32 ]. miR-19b expression levels in LARC biopsies obtained at time of colonoscopy have been identified as an independent predictor of pathological response to preoperative chemoradiation.…”
Section: Discussionsupporting
confidence: 88%
“…miR-19b expression levels in LARC biopsies obtained at time of colonoscopy have been identified as an independent predictor of pathological response to preoperative chemoradiation. miR-19b expression increases in chemotherapy-resistant cells and downregulation of miR-19b enhances the antitumor effects of chemotherapy [ 32 ]. miR-19b was also found to be overexpressed in colorectal tissue, and indicated a poor prognosis.…”
Section: Discussionmentioning
confidence: 99%